2006
DOI: 10.1542/peds.2005-2095
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Enzyme-Linked Immunospot Assay and Tuberculin Skin Test in Healthy Children Exposed to Mycobacterium tuberculosis

Abstract: In Gambian children, the ELISPOT is slightly less sensitive than the TST in the diagnosis of M tuberculosis infection from recent exposure, and neither test is confounded by prior BCG vaccination. Evidence of reduced TST sensitivity in subjects with the lowest known recent M tuberculosis exposure suggests that, when maximal sensitivity is important, the 2 tests may be best used together.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
3
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 23 publications
8
54
3
1
Order By: Relevance
“…These data agree with findings in other studies that have investigated TB outbreaks and study contacts [4,11,[13][14][15][16][17][18]. These results also show the usefulness of IFN-c tests to diagnose LTBI in BCG-vaccinated children when they are screened as part of paediatric or epidemiological control.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These data agree with findings in other studies that have investigated TB outbreaks and study contacts [4,11,[13][14][15][16][17][18]. These results also show the usefulness of IFN-c tests to diagnose LTBI in BCG-vaccinated children when they are screened as part of paediatric or epidemiological control.…”
Section: Discussionsupporting
confidence: 91%
“…In published studies, this threshold can vary greatly, from 5, 10 and up to 15 mm of induration as indicative of TB infection [15,17,19,20,29], and generally depends on population groups (contacts and level of risk of development of active TB), and specific guidelines of the country.…”
Section: Discussionmentioning
confidence: 99%
“…Although somewhat contradictory to reports from adult studies [6,30], the same has been reported from other paediatric cohorts in TB endemic countries [31,32], in which it was concluded that BCG vaccination was not an important cause of false-positive TST, except in communities with low TB prevalence. The findings of the present study are consistent with these observations.…”
Section: Discussioncontrasting
confidence: 81%
“…Notably, the results of a meta-analysis, involving more than 200,000 children in 24 studies, suggest that only 8.5% of individuals BCG-vaccinated in infancy develop a false-positive TST (defined as ≥ 10 mm induration), 43 indicating that BCG vaccination alone is unlikely to account for the large proportions of discordance reported in most pediatric IGRA studies. [44][45][46] In our study, we observed multiple statistically significant differences between the cytokine responses in the uninfected group and the common discordance group. Importantly, these differences were also detected in samples stimulated with ESAT-6 and CFP-10, which cannot be explained by antigenic cross-reactivity, as both peptides are absent from all BCG vaccine strains.…”
Section: Receiver Operating Characteristic Analysesmentioning
confidence: 46%